A Multicomponent Ni-, Zr-, and Cu-Catalyzed Strategy for Enantioselective Synthesis of Alkenyl-Substituted Quaternary Carbons() - McGrath, Kevin P. (2014)
The availability of enantiomerically enriched carbonyl-containing compounds is essential to the synthesis of biologically active molecules. Since catalytic enantioselective conjugate addition (ECA) reactions directly generate the latter valuable class of molecules, the design and development of such protocols represents a compelling objective in modern chemistry. Herein, we disclose the first solution to the problem of ECA of alkenyl groups to acyclic trisubstituted enones, an advance achieved by adopting an easily modifiable and fully catalytic approach. The requisite alkenylaluminum reagents are synthesized with exceptional site- and/or stereoselectivity by a Ni-catalyzed hydroalumination process, and the necessary enones are prepared through a site- and stereoselective zirconocene-catalyzed carboalumination/acylation reaction. The all-catalytic procedure is complete within four hours, furnishing the desired products in up to 77% overall yield and 99:1 enantiomeric ratio.